Implementasi Sistem Absensi QR Code Menggunakan Metode Agile (Studi Kasus: Zea Salon) - Ananda Ivana Anggraini (Journal of Information Systems and Business Technology, 2025)
Employee attendance is a crucial element in human resource management (HRM), particularly in service sectors such as beauty salons. The manual attendance recording process often causes challenges, including delays in data recap, potential information manipulation, and low administrative efficiency. The digitalization of the attendance system is seen as a more appropriate and relevant solution in today's technological era. This study aims to assess the impact of implementing a QR Code-based digital attendance system on employee attendance effectiveness at Zea Salon. The application was developed using PHP programming language with the CodeIgniter framework and MySQL as the database management system. QR Codes are used as unique identifiers for each employee and are scanned upon arrival at work. This research applies a quantitative approach through experimental methods, consisting of three main designs: pre-experiment, quasi-experiment, and true-experiment. Data were collected through documentation, observation, interviews, and questionnaires, and then compared between the conditions before and after the system was implemented. The results show improvements in attendance punctuality, a decrease in tardiness, and a reduction in unexcused absences. The implementation of this system also contributes to more efficient administrative management and supports faster, data-driven decision-making processes.